2015
DOI: 10.17265/1934-7391/2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salinity Stress on Capsicum annuum Callus Growth, Regeneration and Callus Content of Capsaicin, Phenylalanine, Proline and Ascorbic Acid

Abstract: Abstract:The present research was conducted to study salinity effect on callus growth and regeneration from the local Chilli pepper cultivar as well as calli content of capsaicin, phenylalanine, proline and ascorbic acid. The results showed that the Pericarp gave the highest fresh and dry weight of 511.6 mg and 56.95 mg respectively at 9 dSm -1 compared with other interactions. Moreover the lowest fresh and dry weight was recorded for the root calli grown at 12 dSm -1 . The highest regeneration percentage was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Although betaine plays a more important role in higher plants than in algae as osmoprotectant 73 , a transcriptomic study showed that three choline dehydrogenase genes (involved in the conversion from choline to betaine) were upregulated in Ulva compressa during a recovery period after hyposaline stress 74 . We also found an enrichment at high salinity of bacterial genes necessary for the production of the essential amino acid phenylalanine, which is known to accumulate in plants and algae under high salinity conditions 75,76 and increases salinity tolerance in maize 77 .…”
Section: Large Potential For Vitamin B Production By Bacteriamentioning
confidence: 68%
“…Although betaine plays a more important role in higher plants than in algae as osmoprotectant 73 , a transcriptomic study showed that three choline dehydrogenase genes (involved in the conversion from choline to betaine) were upregulated in Ulva compressa during a recovery period after hyposaline stress 74 . We also found an enrichment at high salinity of bacterial genes necessary for the production of the essential amino acid phenylalanine, which is known to accumulate in plants and algae under high salinity conditions 75,76 and increases salinity tolerance in maize 77 .…”
Section: Large Potential For Vitamin B Production By Bacteriamentioning
confidence: 68%
“…Water deficit will increase the activity of capsaicin synthase which will increase the synthesis of capsaicin synthesis in chili [30]. Al-Hattab et al [20] also reported that when plants are exposed to salt stress would accumulate secondary metabolites and amino acids as a defense mechanism. Thus, the accumulation of capsaicin allows the chili pepper tolerate to saline soil.…”
Section: Growth Charactersmentioning
confidence: 99%
“…Additionally, Purwaningrahayu [19] reported that the accumulation of proline as a parameter of salinity stress can be detected by an increase in proline levels due to increased salinity stress. Proline is an osmoprotectant compound that plays a role in maintaining cell stability through osmotic and oxidative regulation [20]. Proline also serves as a signaling molecule when plants respond to unfavorable conditions [21].…”
Section: Physiological Responsementioning
confidence: 99%